Assessment of lead and cadmium exposure through olive and corn oil consumption in Gonbad-Kavus, north of Iran: A public health risk analysis - Janan Tayeb; Mohammadhosein Movassaghghazani (Toxicology Reports)
Lead and cadmium are common heavy metals in oils. This study assessed their levels in commercial and traditional olive and corn oils from Gonbad-Kavus City using graphite furnace atomic absorption spectrometry after microwave digestion. Hazard Quotient (HQ) and Hazard Index (HI) were calculated. The results from 60 oil samples showed quantifiable levels of lead and cadmium in all samples. Lead concentrations in commercial olive oil, traditional olive oil, commercial corn oil, and traditional corn oil were 13.27 ± 3.37, 17.48 ± 4.82, 19.27 ± 8.12, and 32.40 ± 6.13 μg/kg, respectively. Cadmium concentrations were 4.14 ± 0.53, 3.50 ± 0.72, 4.48 ± 1.80, and 5.77 ± 1.34 µg/kg, respectively. All lead levels were below the 80 µg/kg limit set by the Institute of Standards and Industrial Research of Iran (ISIRI). For a 70 kg person consuming 0.147 g of corn oil and 0.328 g of olive oil daily, the metals pose no risk to health over a lifetime. No health concerns were found for oils except traditional olive oil. Corn oil showed significant lead contamination. HI values for lead and cadmium in oils were below 1, indicating no non-carcinogenic health risk. MOE values for lead in traditional olive oil were below 10,000, while other oils were above, indicating no significant risk to consumers. These findings call for a review of national standards and increased monitoring of heavy metals in vegetable oils in the region.